KONTRIBUSI REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR SENAM LANTAI SISWA KELAS VII DI SMP NEGERI 1CIKAMPEK - Beriana Hutri Yanti Damanik; Ardawi Sumarno; Rizki Aminudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the contribution of reward and punishment to the learning motivation of floor exercise among seventh-grade students at SMP Negeri 1 Cikampek. The background of this research is based on the importance of implementing reward and punishment to increase students' enthusiasm for learning, especially in practical lessons such as floor exercise which requires discipline and high motivation. This research employs a descriptive quantitative method with a survey approach. The population of this study is all seventh-grade students of SMP Negeri 1 Cikampek, with a sample size of 48 students. The data were collected using a Likert scale questionnaire and analyzed using descriptive statistical techniques in the form of frequency distribution and percentage. The results showed that most students gave positive responses to reward, with the majority choosing the categories of agree and strongly agree. Meanwhile, the implementation of punishment is still considered relevant but must be applied wisely. Students' learning motivation in floor exercise is categorized as high. This indicates that reward and punishment provide a positive contribution in shaping students' learning motivation.